Agency conflicts in innovation adoption: Lessons from the airline industry - Alberto Urue\~na; Manuel Sáenz; Antonio Hidalgo Nuchera (Journal of Innovation & Knowledge (JIK), 2024)
Introducing an innovation does not end, but rather starts, with adoption. In fact, some innovations display network elements and require more than one firm to take them up in order to be successful and deliver the intended results. Such is the case of NDC (new distribution capability), an airline-fostered enhancement of the way air travel services are conveyed and distributed from carriers to travel agents. The promise behind NDC is that travel services will be sold more richly and within a more open and inclusive framework. We draw on the diffusion of innovations, institutional theory, and agency theory to review the determinants of adoption and its effects on performance for service providers. We use the International Air Transport Association (IATA) ticket database to establish the role that institutional pressure plays on innovation behaviours and firms' results. We find that institutional pressure, not just innovation attributes, influence outcomes. Also, given each player's different incentives and the asymmetry of information, ticket sales are selectively distributed in ways that fit the agent and only occasionally the airline principal. Thus, we conclude that travel intermediaries assess outcomes wholistically and that the innovation's revenue uplift depends on such assessment.
Keywords: O00; O30; O32; 650; Airline distribution; Innovation results; Agency theory; Incentives management; Classification codes